Exploring, defining, and illustrating a concept: Structural and psychological empowerment in the workplace. Issue 4 (17th October 2018) - Abel, Sarah E.; Hand, Mikel W.
Abstract: Aim: The aim of this concept analysis is to clarify the meaning and relationship of psychological and structural empowerment. Background: Empowerment is linked to positive organizational and individual constructs and outcomes. Improving the work environment may assist in sustaining a fragile and essential workforce. Design: Walker and Avant's method was used to guide an analysis of this concept. Data Source: Resources published from 1970 to 2018 were identified via electronic databases, empirical works, and modern operational usage of the terms. Review Methods: A literature review and search for concept maps were completed and analyzed to identify uses and definitions of the concept: attributes, antecedents, consequences, and empirical referents. It also includes identifying model, borderline, and contrary cases to differentiate empowerment from other related concepts. Results: A comprehensive, inclusive review of empowerment must include both constructs, structural and psychological. A conceptual map of these akin constructs illustrates their syndication. Conclusions: The concept of examining empowerment from both constructs, structural and psychological, is necessary to develop evidence‐based practice strategies and improve the work environment and workforce.